2019
DOI: 10.1177/1090198118820095
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the VAMOS Strategy for Increasing Physical Activity and Healthy Dietary Habits: A Randomized Controlled Community Trial

Abstract: This study aimed to evaluate the effectiveness of the VAMOS strategy (Health-Improving Active Life) in improving physical activity (PA), dietary habits, and anthropometric variables of primary health care (PHC) users in Brazil. A randomized controlled community trial was conducted at two units of the Health Academy Program (HAP; a service provided by PHC), which were randomly assigned either to control group (CG) or intervention group (IG). Participants in both groups (CG = 156 and IG = 135) took part in physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
25

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 30 publications
2
27
0
25
Order By: Relevance
“…Contudo, 59,1% dos servidores concluíram a intervenção. Outros estudos com o Programa VAMOS também apresentaram taxas inferiores a 50% 20,21 . Estudo realizado na Atenção Primária à Saúde que avaliou a permanência de idosos no VAMOS verificou que a taxa foi de 51,9%, sendo relacionada ao estado civil dos participantes 22 .…”
Section: Discussionunclassified
“…Contudo, 59,1% dos servidores concluíram a intervenção. Outros estudos com o Programa VAMOS também apresentaram taxas inferiores a 50% 20,21 . Estudo realizado na Atenção Primária à Saúde que avaliou a permanência de idosos no VAMOS verificou que a taxa foi de 51,9%, sendo relacionada ao estado civil dos participantes 22 .…”
Section: Discussionunclassified
“…Studies on the VAMOS Program have shown positive results, such as the reduction in sedentary behavior, an increase in mild PA, an increase of 10% in PA time with a moderate/vigorous intensity, lower consumption of industrialized seasonings, and an increase in the consumption of raw vegetables. These results have had a direct influence on participants' quality of life 26,27 .…”
Section: Discussionmentioning
confidence: 92%
“…Em cada encontro foi desenvolvida uma temática específica (Quadro 1) mediada por um profissional previamente treinado. Detalhamento metodológico do estudo está publicado em Meurer et al (2019). Para este estudo foram conduzidos três Grupos Focais (GFs), com até 11 participantes cada.…”
Section: Metodologiaunclassified
“…O VAMOS tem-se mostrado efetivo em relação aos principais desfechos (AF e AS). Ensaios controlados e randomizados mostraram 03 redução do comportamento sedentário, aumento da AF leve e incremento de 10% no tempo de AF em intensidades moderada/vigorosa (GERAGE et al, 2017), menor consumo de temperos industrializados, aumento do consumo de verduras e legumes (MEURER et al, 2019) e melhora na percepção da qualidade de vida (QV). Alguns resultados apontam que a metodologia empregada foi um facilitador para a mudança nos comportamentos (TONOSAKI et al, 2018).…”
Section: Introductionunclassified
See 1 more Smart Citation